Minimal multi-camera system for perception of deformable shapes - Herguedas Gastón, Rafael; López Nicolás, Gonzalo; Sagüés Blázquiz, Carlos (Jornada de Jóvenes Investigadores del I3A, 2019)
Within the context of autonomous manipulation of deformable objects, we propose a minimal multi-camera perception system that allows to cover a deforming 2D shape over time according to a specific visibility objective. Our method iteratively solves an optimization problem that includes collision avoidance and robust visibility constraints.